A multidimensional analysis of prognostic factors in atopic dermatitis - Liu, Zhenggang; Guo, Mengnan; Li, Yumei; Xu, Hui (Frontiers in Medicine, 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin condition with a high prevalence worldwide and multifaceted pathogenesis. In general, patients with moderate to severe AD often experience relapse after discontinuing treatment. Therefore, to understand the possible factors of chronic relapse of AD and to look for biological markers that predict the relapse or poor prognosis of AD will be helpful for clinical treatment. Mutations in genes such as FLG, SPINK5, STAT, KIF3A, claudin-1, Ovol1, and HLA-DRB1 offer new insights into the genetic basis of AD. Routine factors may help improve patient lifestyle, highlight the importance of environmental influences (including psychological stress), and support clinicians in optimizing anti-infective treatment strategies. The inflammatory axis (CD30–CD30L axis, IL-9-IL-18 axis) provides new insights into the inflammatory pathways of AD and may be a target for future therapies. Low NKG2D expression may have adverse effects on prognosis. Prognostic biomarkers can play an important role in treatment monitoring, disease progression and recurrence, and provide the possibility for more personalized treatment.